(untitled) (Journal of the College of Basic Education, 2026)
The technique of repetition is one of the most prominent musical phenomena in the poetry of Mohsen Abu Al-Hub Al-Kabir, because it adds aesthetic and semantic energy to the text. The rhythmic repetition in his poetry was not a formal feature but a stylistic one that contributed to shaping the internal rhythm of the text through musical cohesion and intensifying the semantic dimension, as well as linking the rhythm to the emotional state of the poet. The study required that the descriptive analytical approach be used to address it, in order to monitor and analyze the patterns of repetition in Abu Al-Hub’s poetry, and to understand the emotional state and its impact on the recipient. The study also succeeded in revealing its patterns and functions, and in demonstrating the extent of the impact of repetition on the psychological and intellectual state that Abu Al-Hub wanted to convey in his poetic texts